Poaceae Diseases Detection using Machine Learning - Adhikari, Aayush; Bishwakrama, Bisoj; Regmi, Charchit; Giri, Dipesh; Sharma Dahal, Suramya (KEC Journal of Science and Engineering, 2024)
Agriculture is the number one supply of livelihood for approximately more than 66% of the Nepali population and Poaceae class is one of the most important meal grains of Nepal. Poaceae plant sicknesses are the major causes to lessen the manufacturing & goodness of meals. Nutrient deficiency of Nitrogen, Potassium and Phosphorus.can also cause plants to not grow to their full strength. Identification and preventing such diseases as well as nutrient deficiency can enhance the growth of Poaceae plants.